The Engineering Pedagogy Evolution: The Foundation and Three Measurements - D. P. Danilaev; N. N. Malivanov (Высшее образование в России, 2021)
The status, subject area and structure of engineering pedagogy are still at the center of the academic and scientific community. It develops as a professional pedagogy section, although it tended to be viewed as an educational module, as a field of teacher practical activity. The role of engineering pedagogy in developing engineering thinking should become increasingly important, taking into account the integration processes – inter-disciplinary, inter-subject, trans-professional, and the transformations in the industrial sphere in general and in engineering in particular. The transfer of its accumulated experience and ideas to new application areas can enrich other branches of knowledge with ideas, principles and cognitive approaches. Both methods of acquiring scientific knowledge and heuristic and practical technologies are equally essential for the system of continuous fundamental engineering and technical education development. Engineering pedagogy’s goals revision and clarification lead to a multidimensional space for engineering thinking development, including training of engineering educators for a lifelong learning system. Based on the general foundations and laws of pedagogy, three measurements of engineering pedagogy enable to reveal its interdisciplinary strategy in different subject areas. Engineering pedagogy can participate in various formats– as teacher training technology both for school and university teachers.